Internal Bank Factors and Financing Distribution: Evidence from Islamic Commercial Banks - Widyasari, Rieke Meinar; Fathurrohman, Muhamad Said (Jurnal Ekonomi Syariah Teori dan Terapan, 2025)
This study aims to analyze the effect of BOPO, CAR, NOM, and DPK on the distribution of financing in Islamic commercial banks in 2014: Q1 - 2024: Q3. The method used in this research is quantitative research method with panel regression analysis technique. The sampling technique used purposive sampling and obtained 10 Islamic banks as samples. By using data sources from quarterly financial reports on each bank's website and publications on the OJK website. Partial research results in this study indicate that BOPO, CAR, and NOM have a significant and negative influence on financing distribution. Meanwhile, DPK has a significant and positive influence on the distribution of financing. The implication of this research is that Islamic banking should optimize operational efficiency, productive asset management, and liquidity management, and that regulators should determine and evaluate related policies to encourage financing distribution.